Aesthetics in implantology - A., Shajahan P.; Raghavan, Rohit; P., Faseela P. (International Journal of Research in Medical Sciences, 2025)
The field of dentistry has been transformed by osseointegrated implants, providing a dependable and lasting solution for patients who have lost teeth. These implants are now a highly successful and widely accepted treatment. Historically, the success of implant placement depended heavily on the quantity and quality of existing bone. However, with innovations like guided tissue regeneration (GTR) and new tools such as Osseo densification burs, it's now possible to place implants successfully even in areas with less-than-ideal bone. When placing implants in these more challenging locations, the focus extends beyond just functional success to include crucial esthetic considerations. These include the shape of the alveolar ridge contour, the health of the surrounding mucosa, the position of the crown margin, the crown form, the interdental spacing, how the occlusal surface design, the placement of the incisal edge positioning, how the lip supports, and the overall appearance of the smile.